Bentuk dan Fungsi Ilustrasi dalam Naskah-Naskah Kaghas Koleksi Peti 93 PNRI: Kajian Kodikologis - Muhammad Haidar Izzuddin; Munawar Holil (Perpustakaan Nasional RI, 2023)
Illustrations can be found in a number of kaghas/bark manuscripts in box 93 of the National Library of the Republic of Indonesia. These are manuscripts 93 E 95, E 99, E 102, E 106, E 109, E 100, and E 956. These illustrations have various forms in each kaghas text. This study aims to explain the form and function of the illustrations of kaghas manuscripts in box number 93 of the National Library of the Republic of Indonesia). This research is codicological research and uses a qualitative descriptive method. The results obtained from the research are illustrations in kaghas manuscripts consisting of three forms, namely visual text forms, symbolic forms, and abstract forms. These illustrations have an aesthetical function as text visualization and decoration, a practical function as a calculation, and a magical function as a tattoo.